Tiger mother and her cubs on a stage:: ‘Tiger’ parenting style and its effects in Listen to Me - Stefanny Irawan (k@ta: A Biannual Publication on the Study of Languange and Literature, 2019)
Ever since the publication of Amy Chua’s memoir, Battle Hymn of The Tiger Mother, in 2011, Asian or Asian-heritage parenting has received more time under the limelight both in and out of the United States. More attention is given to the effects of that particular parenting style on the children’s academic achievement and wellbeing. Listen to Me (LTM), a play by Bernadeth Febyola Linando (2018) published as one of Petra Little Theatre’s New Play Development Series, indicates that the issue also hits a nerve among young contemporary Indonesian playwrights. This paper is interested in finding out how LTM portrays Tiger Mother parenting style and its impact on the children. Upon analyzing the play using the conceptual framework of parenting styles and their impacts, this paper argues that LTM displays a typical Tiger Mother parenting similar to Chua’s with a slight difference, and it shows mainly negative results of such parenting on the main character, and, on the side, some positive results on two other supporting characters.